Knowledge about Maintaining Dental and Oral Hygiene Before and After Counseling Using Flipchart Media for Class IV Students at SDN 060825 Medan Area District - Emmelia, Emmelia; Simaremare, Susy Adrianelly (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2023)
Knowledge about maintaining oral hygiene is one of the efforts to improve health. Flipchart media is a communication medium that can change children's behavior towards their knowledge. Knowledge is very important in underlying the formation of attitudes and behaviors that support or do not support health, especially dental and oral health. This study aims to determine knowledge about maintaining oral hygiene before and after counseling using flipchart media for grade IV students at SD Negeri 060825 Jalan Ismaliyah No.83 Kota Matsum, Medan Area Sub District. This type of research was descriptive with a survey method that is carried out by distributing questionnaires. The sample of this study were 30 grade IV students. The results of this study indicate the knowledge of students about maintaining dental and oral hygiene before counseling is carried out, namely 1 person (3.3%) good criteria, 22 people (73.3%) moderate criteria and 7 people (23.3%) bad criteria %). After counseling was carried out on students, namely good criteria as many as 29 people (96.6%), moderate criteria as many as 1 person (3.3%). The conclusion of this study showed that there is a change in students' knowledge of dental and oral hygiene prior to counseling through flipchart media. Knowledge of students were in moderate category (73.3%) and after being given knowledge counseling students was in good category (96.6%).